2021
DOI: 10.1016/j.toxrep.2021.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in soils and edible tissues of Lepidium meyenii (maca) and health risk assessment in areas influenced by mining activity in the Central region of Peru

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 87 publications
2
14
1
1
Order By: Relevance
“…For example, Hayford Svoboda et al, (2006), and Zhuang et al, (2009a, 2009b, reported elevated trace elements in agricultural soils and crops from mining areas in the Czech Republic and China, respectively. Similar findings were informed in areas influenced by mining activity in the central region of Peru, where the mean concentration of Cd (0.32 ± 0.23 mg kg −1 ) and Pb (0.20 ± 0.12 mg kg −1 ) in Lepidium meyenii Walpers (maca) samples exceeded the values established by the FAO/WHO guideline (Orellana Mendoza et al, 2021). In contrast, Marrugo-Madrid et al ( 2022) determined trace element contents below the threshold established in the regulations in fruits and tubers collected in the gold mining area of Colombia.…”
Section: Trace Elements Content In Soil Samplessupporting
confidence: 81%
See 1 more Smart Citation
“…For example, Hayford Svoboda et al, (2006), and Zhuang et al, (2009a, 2009b, reported elevated trace elements in agricultural soils and crops from mining areas in the Czech Republic and China, respectively. Similar findings were informed in areas influenced by mining activity in the central region of Peru, where the mean concentration of Cd (0.32 ± 0.23 mg kg −1 ) and Pb (0.20 ± 0.12 mg kg −1 ) in Lepidium meyenii Walpers (maca) samples exceeded the values established by the FAO/WHO guideline (Orellana Mendoza et al, 2021). In contrast, Marrugo-Madrid et al ( 2022) determined trace element contents below the threshold established in the regulations in fruits and tubers collected in the gold mining area of Colombia.…”
Section: Trace Elements Content In Soil Samplessupporting
confidence: 81%
“…The concentrations of Cd and Zn from Ponce Enriquez were in the range reported by Orellana Mendoza et al (2021) in areas influenced by mining activity in the central region of Peru; yet, the content of Pb (72.11 ± 15.43 mg kg −1 ) was lower in our study. In contrast, the As concentration in the previously mentioned research (20.85 ± 5.79 mg kg -1 ) was several times lower than ours.…”
Section: Trace Elements Content In Soil Samplescontrasting
confidence: 53%
“…Another point to consider with the use of the maca tuber is its ability for the root of a plant to accumulate heavy metals from the soil where it is grown. It has been documented that maca can contain toxic metals due to soil contamination from the mining industry in Peru [ 79 ] or potentially from naturally high levels of heavy metals due to prehistoric lava flows and soil formation [ 80 ]. Specifically, it may be grown in soil with relatively higher concentrations of metals like nickel [ 81 ], arsenic, cadmium, and lead [ 79 ].…”
Section: The Significant Role Of Environmental Factors and Processing...mentioning
confidence: 99%
“…It has been documented that maca can contain toxic metals due to soil contamination from the mining industry in Peru [ 79 ] or potentially from naturally high levels of heavy metals due to prehistoric lava flows and soil formation [ 80 ]. Specifically, it may be grown in soil with relatively higher concentrations of metals like nickel [ 81 ], arsenic, cadmium, and lead [ 79 ]. One study analyzed yellow and purple maca for toxic metals and essential minerals and concluded that cadmium and lead concentrations in both the soil and hypocotyls exceeded permissible limits [ 79 ].…”
Section: The Significant Role Of Environmental Factors and Processing...mentioning
confidence: 99%
“…Food crops are able to absorb several heavy metals from the soils they are cultivated in depending on the physicochemical properties of the soils such as pH, organic matter content, clay fraction, mineral composition and the binding capacity of the soil [ [14] , [15] , [16] ]. Dheri et al [ 17 ] have explained that heavy metals dissolved in waste water and water bodies are easily transported to suspended solids.…”
Section: Introductionmentioning
confidence: 99%